PENERAPAN TRIPLE EXPONENTIAL SMOOTHING DALAM MERAMALKAN LAJU INFLASI BULANAN PROVINSI ACEH TAHUN 2019 - 2020 - Fitria, Viza; Anwar, Samsul (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
The inflation rate is the percentage increase or decrease in the price of goods and services in general in a particular region. The general increase in the inflation rate is caused by an increase in the money supply that exceeds economic growth, the rupiah exchange rate, and also a high demand for goods. Triple Exponential Smoothing method is one of the forecasting methods in time series data that is used when data shows the existence of seasonal trends and behavior. The purpose of this study is to forecast the monthly inflation rate of Aceh Province in 2019-2020. The data used is the monthly inflation data of Aceh Province starting from January 2011 to December 2018. The best Triple Exponential Smoothing model for forecasting the inflation rate is a model with alpha (?) = 0.045, beta (ß) = 0.034, and gamma (?) = 0.49. The results show that forecasting data tends to follow the previous data pattern. The monthly inflation rate in Aceh Province tends to rise in June and December and is low in February to April. The monthly inflation rate of Aceh Province in 2019 is expected to be in the range of -0.41 to 0.71. Wh ile in 2020, the inflation rate of Aceh Province is estimated to be in the range of -0.47 to 0.65.